TECHNICAL SKILLS OF PRIMARY SCHOOL PUPILS IN SLOVAKIA - BANESZ, Gabriel; LUKACOVA, Danka (Journal of Technology and Information Education, 2025)
Technical skills are part of elementary education in most primary schools worldwide, including the Slovak Republic. In Slovakia, the development of these skills begins in pre-primary education and continues in primary schools. Mastery of the technical skills necessary for further education, personal life, and professional life is dependent on the material and technical equipment of schools. In the years 2013-2015, two national projects were implemented in Slovakia, providing equipment to 226 schools for teaching the subject of Technology. This article examines whether these schools utilize the provided equipment for practical education of students. The aim of the research was to assess the level of practical skills among 7th-grade students through observation, which was conducted on a sample of 83 students. It was found that all respondents achieved a 70% level of skills in all observed areas. The article further provides a detailed analysis of the students' skills.
Keywords: Technical skills; material and technical equipment of schools; analysis.